# (3-x)/-4=(x+6)/3

I have tried this one multiple times but i still can't get it.

## (3-x)/-4 = (x+6)/3

subtract the terms on the right over to the left (everything)

[(3-x)/-4]-[(x+6)/3]=0

find a common denominator

for 4 and 3 which is 12

[-3(3-x)/12]-[4(x+6)/12]=0

multiply over

(-9+3x)/12 - (4x+24)/12= 0

[(-9+3x)-(4x+24)]/12 = 0 don't forget the negative

(-3+3x-4x-24)/ 12 = 0

combine like terms on the numerator then solve for x

(-3+3x-4x-24)= 0

## Typo after multiply over: Correction

is it's -9 not negative -3

[(-9+3x)-(4x+24)]/12 = 0 don't forget the negative

(**-9 +3x-4x-24)/ 12 = 0 **

combine like terms on the numerator then solve for x

(-9+3x-4x-24)= 0

## To solve the equation (3-x)/-4=(x+6)/3, we can start by cross-multiplying. This means multiplying the numerator of the left side expression with the denominator of the right side expression, and vice versa.

First, cross-multiplying the left side:

(3-x) * 3 = -4 * (x+6)

Expanding both sides:

9 - 3x = -4x - 24

Next, we can simplify the equation by combining like terms. To do this, let's isolate the variables on one side of the equation and the constants on the other side.

Adding 4x to both sides:

9 + x = -24

To isolate the x-term, we need to get rid of the constant on the left side. By subtracting 9 from both sides, we have:

x = -33

Therefore, the solution to the equation (3-x)/-4=(x+6)/3 is x = -33.